2015
DOI: 10.5797/jnet.cr.2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic aneurysm of the middle meningeal artery presenting with traumatic middle meningeal arteriovenous fistula: a case report

Abstract: Objective: Traumatic arteriovenous fistula (AVF) concomitant with pesudoaneurysm involving the middle meningeal artery is uncommon. Traumatic AVF is also known to occasionally show spontaneous closure. We report a rare case of traumatic pseudoaneurysm of the middle meningeal artery identified after spontaneous closure of a traumatic AVF. Case presentation: A 36-year-old right-handed man suffered a head injury after falling from a step at home, and was brought to our institute. The patient showed no neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…For embolization, the use of embolic agents such as Onyx and Embosphere (Merit Medical, South Jordan, UT, USA) has been reported 12) in addition to NBCA, 9) which was used in our patient. According to the above report, Almefty et al 4) achieved cure in eight of nine patients with MMAVF by embolization using Onyx.…”
Section: Discussionmentioning
confidence: 84%
“…For embolization, the use of embolic agents such as Onyx and Embosphere (Merit Medical, South Jordan, UT, USA) has been reported 12) in addition to NBCA, 9) which was used in our patient. According to the above report, Almefty et al 4) achieved cure in eight of nine patients with MMAVF by embolization using Onyx.…”
Section: Discussionmentioning
confidence: 84%
“…[ 2 ] Most cases were associated with skull fractures, seven with epidural or subdural hematomas, three with multiple drainages from the MMV, and one with an MMA-to-MMV shunt [ Table 1 ]. [ 1 , 2 , 6 , 9 , 10 , 12 ] Among the patients who underwent endovascular treatment, coil embolization alone was performed only for the patients included in the present study. Coils and liquid embolic material were used in the remaining cases.…”
Section: Discussionmentioning
confidence: 99%
“…MMAVF is a relatively rare disease, with typically post-traumatic or iatrogenic origins, [1][2][3][4][5][6] but rare idiopathic cases have also been reported. 2,4) A previous report has shown that most cases of traumatic MMAVF occurred due to a tear in the artery wall caused by a skull fracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, rare cases with an idiopathic origin have also been reported. [1][2][3][4][5][6] MMAVF is suspected based on symptoms, such as tinnitus, bruit, exophthalmos, and findings of dilated vessels on MRI, and is diagnosed using DSA. 5,6) Segmental arterial mediolysis (SAM) is a rare vasculopathy characterized by an unusual noninflammatory and nonatherosclerotic disorder of the arterial medial layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation